Respuesta :

Answer: D

Step-by-step explanation:

Consider the first equation. Subtract 3x from both sides.

y−3x=−2

Consider the second equation. Subtract x from both sides.

y−2−x=0

Add 2 to both sides. Anything plus zero gives itself.

y−x=2

To solve a pair of equations using substitution, first solve one of the equations for one of the variables. Then substitute the result for that variable in the other equation.

y−3x=−2,y−x=2

Choose one of the equations and solve it for y by isolating y on the left hand side of the equal sign.

y−3x=−2

Add 3x to both sides of the equation.

y=3x−2

Substitute 3x−2 for y in the other equation, y−x=2.

3x−2−x=2

Add 3x to −x.

2x−2=2

Add 2 to both sides of the equation.

2x=4

Divide both sides by 2.

x=2

Substitute 2 for x in y=3x−2. Because the resulting equation contains only one variable, you can solve for y directly.

y=3×2−2

Multiply 3 times 2.

y=6−2

Add −2 to 6.

y=4

The system is now solved.

y=4,x=2

Answer:

Step-by-step explanation:

y=3x-2                  ---------------------(1)

y-2=x                    ---------------------(2)

substituting (2) in (1),

y=3x-2

y=3(y-2)-2

y=3y-6-2

-3y+y=-6-2

-2y=-8

∴ y=4                       ----------------------(3)

substituting (3) in(2)

y-2=x

x=4-2

∴x=2

hence,(2,4)

HOPE IT HELPS YOU!!!!